Quantum cage - Bunn, T. Davis, 1952- (Severn House, 2025)
A team of scientists working on a secret NASA-funded project involving quantum theory bring in accountant Darren Costa to deal with some complex federal paperwork. But when the group reveal that they have accidentally established a communication link across space and time to four aliens, Darren suddenly finds himself becoming far more involved in their work than he expected. In the scientists' glass cage, Darren connects to the aliens and their planet through a series of dream-like visions. Is it possible that an incomplete mathematical formula shared by the aliens is the key to unlocking secrets that could prevent Earth's future extinction and ensure humanity's survival? One thing's for certain, with both humans and aliens facing enemies determined to stop them at any cost, solving the puzzle is now a matter of life and death . . .